Efforts to Improve Student Learning Outcomes Using the Project-Based Learning Model in PAI and BP Subjects - Abdul Qodir; Yani Tamala; Ridwan Setiawan; Adib Rubiyad (CV. Edujavare Publishing, 2026)
The Project Based Learning model is an innovative, student-centered learning model, where students are actively involved in solving problems or completing authentic and meaningful projects. In this context, this study aims to explore the application of the Project Based Learning model in Islamic Religious Education (PAI) learning as an effort to improve student learning outcomes and the effectiveness of student creativity. The purpose of this study is to determine efforts to improve student learning outcomes by using the project-based learning model in Islamic Religious Education and Social Studies subjects at SDN 11 Cilegon City. The method of this study is PTK. PTK is an abbreviation of Classroom Action Research. Classroom Action Research is a research method carried out by teachers in their own classes to improve the learning process and improve student performance. The results of this study indicate that the achievement of student learning outcomes after participating in the learning process is still in the category of not being fully optimal. Based on the minimum completeness criteria (KKM) of 75, data obtained show that some students have achieved learning completeness, while others have not. Students who achieve a score of ≥ 75 are declared complete, while students with scores below the KKM are declared not yet complete. This condition indicates that there is variation in students' academic abilities, and shows that the learning process implemented needs to be increased in its effectiveness in order to be able to improve learning outcomes evenly.